Cartografia da percepção de mês e profissionais sobre a atenção a saúde de crianças/adolescentes soropositivos no município de Natal - Silva, Richardon Augusto Rosendo da (2006)
This study had as objective to identify to the perception of mothers and professionals of health on the attention to the health of HIV-Positive children/adolescents in the city of Natal-RN. It is a descriptive-exploratory study with quantitative and qualitative approach, carried through in the Giselda Trigueiro Hospital and in the State and Municipal Health Councils in Natal - RN, from march to december of 2005. The sample was composed by 56 participants, 33 mothers of children who use specialized assistance and 23 professionals. Data collection occurred with the application of a half-structuralized interview. Quantitative data were analyzed through descriptive statistics and qualitative data were submitted to content analysis. Prevailing categories in relation to the cartography of the attention to seropositive children and adolescents in Natal were: Organization and dynamics of the attention; Institutional management and human development; Control and prevention; other contexts of attention; relationship/communication team-patient and organization and functioning of the services. The profile epidemiologist of the children, adolescents and of the people/mothers, who take care of them with HIV/Aids, followed the evolution of the epidemic in the country and the world. It was verified that mothers need care and information; however they make a positive evaluation of the attendance they receive. It was also observed many gaps in the services of assistance, in which the researched group was attended, beyond imperfections in the communication between health professionals and users. The professionals recognize the advances that the politics represent for the assistance of people with Aids; however feel themselves limited by the precariousness of the system and the partner-economic conditions of the people. According to these data, it can be verified great challenges to go through in the context of integrality of the assistance to HIV positive children and adolescents in the city of Natal and in the improvement of the communication in the institution of reference